The Use of Hedges in Tertiary EFL Students' Presentation - Ihsan Nur Iman Faris (English Review: Journal of English Education, 2015)
The main objective of language education is to enable students to communicate effectively. In order to achieve that objective, students need to master pragmatic competence. One of the pragmatic competences which needs to be mastered by students is the ability to use hedging devices. This ability is even more essential for students in tertiary level of education due to the some conventions which need to be followed. Failures in using hedges properly can threat the face of students and other stakeholders in academic contexts. This research aims at investigating how hedges are used by the tertiary students when addressing questions in a discussion session of a presentation. This research is a qualitative research employing interaction analysis method. The participants in this research were nine students of Language in Use course of master of English education program in a state university in Bandung. The findings demonstrate that hedges were found in all questions addressed to the presenters and the lecturer. Introductory phrases were the most frequently-used forms used to hedge and hedges function mostly to attenuate epistemic commitment in addressing questions. Although hedges were used when addressing questions in a discussion session of a presentation, some findings indicate that the hedges were not entirely in line with academic conventions. Based on the findings, the recommendations given are 1) that further research on the use of hedges in academic contexts be conducted, 2) teachers and lecturers raise students’ awareness of the importance of pragmatic competence, and 3) teachers and lecturers give more concerns to provide students with pragmatic competence.Keywords: pragmatic competence, hedges, questions, academic contexts.